Inclusão perversa: trabalho infantil de estudantes na cidade de São Paulo - Carvalho, Martha M. G. de (2005)
"Wicked Inclusion: child labor of students in the city of São Paulo" discusses the matter of the wicked insertion that characterizes the child labor in the nowadays society in big cities, such as São Paulo. In this way, the research that has been made came from the idea that what characterizes the children and teenagers submitted to the dynamics of child labor is their precarious urban insertion. For this purpose, it has been tried to find how that happens in the neighborhoods of the periphery of the city. The universe that has been researched, Paraisopólis and Cidade Tiradentes, are located in places marked by the precarious conditions of life and housing and/or irregular and disordered settlements of its population. The study proposed aimed to analyze the portion of the population that works and study, evaluating the situation of the families involved in the phenomenon of the child labor. It has been tried to characterize the situation of the children and teenagers - aged between 7 and 14 years old - paying attention for the involvement of the families: in productive activities and in their strategies. In particular, it has been a special concern to verify how the universe of children and teenagers articulate itself with the representations about the work and their meanings. In order to obtain a more deepened and wide-ranging discussion of the problems related with the object of study, it has been introduced the technique of the focal groups. This doctoral thesis presented here, aimed , therefore, to discuss the articulation that exists between the factors of socio-spatial segregation , that express the inequalities presents in the structuration of the city with the processes of wicked social inclusion that create the growth of the child labor in the city of São Paulo.